2019
DOI: 10.3126/ajms.v10i4.24176
|View full text |Cite
|
Sign up to set email alerts
|

Device closure of ventricular septal defect: Initial experience in Nepal

Abstract: Background: Device closure is an attractive alternative in the management of Ventricular Septal defect (VSD). Aims and Objective: The aim of the study was to access the safety and early outcome of VSD device closure at Shahid Gangalal National Heart Centre, Nepal. Materials and Methods: The study was single center, retrospective study. All the VSD cases who were attempted for VSD device closure during December 2016 to February 2019 were included. Catheterization laboratory records for VSD type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The present study showed that, according to VSD types, 19 cases (54.3%) were perimembranous, 12 cases (34.3 %) were muscular and 4 cases (11.4%) were basal muscular. This is in agreement with Adhikari et al (8) who reported that there was perimembranous VSD in 49 cases (89%) and muscular VSD in 6 (11%) patients. While, in the study of Khoshhal et al (1) they reported that 68.6% of the studied children had muscular VSD and 31.4% were diagnosed by perimembranous VSD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that, according to VSD types, 19 cases (54.3%) were perimembranous, 12 cases (34.3 %) were muscular and 4 cases (11.4%) were basal muscular. This is in agreement with Adhikari et al (8) who reported that there was perimembranous VSD in 49 cases (89%) and muscular VSD in 6 (11%) patients. While, in the study of Khoshhal et al (1) they reported that 68.6% of the studied children had muscular VSD and 31.4% were diagnosed by perimembranous VSD.…”
Section: Discussionsupporting
confidence: 93%
“…18 cases (51.4%) of the study population were females and 17 cases (48.6%) of the study population were males. In Adhikari et al (8) study, they reported that the mean age of the patient was 11.1 years. 29 (52.7%) were females and 26 (47.3%) were males.…”
Section: Discussionmentioning
confidence: 95%
“…As studies have shown low mortality and morbidity with the percutaneous approach, device closure of VSDs has been gaining more attention. [4,5] With the availability of different devices, the range of closure had been expanded from muscular to perimembranous and subarterial VSDs. Among various complications associated with device closure, aortic regurgitation is considered to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cardiologists, at our center are performing significant number of transcatheter closure of ASD as well as VSD. 18,19 Overall, the impact of transcatheter closure of isolated cardiac lesion to the number of surgical closure in our center is not studied yet.…”
Section: Discussionmentioning
confidence: 99%